2017
DOI: 10.1038/s41598-017-05468-w
|View full text |Cite
|
Sign up to set email alerts
|

Free immunoglobulin light chain (FLC) promotes murine colitis and colitis-associated colon carcinogenesis by activating the inflammasome

Abstract: Numerous studies have demonstrated that free Ig light chain (FLC), a novel inflammation mediator, participates in many inflammatory diseases by activating mast cells and extending the survival of neutrophils. However, it remains unclear whether FLC is involved in colitis and colitis-associated colon carcinogenesis (CAC). In this study, we found a significant increase in FLC in murine models of DSS (Dextran Sulfate Sodium Salt)-induced colitis and CAC compared to controls. Peptide F991, a functional blocker of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…In addition, cancer-derived IgG is identified as a functional component of pancreatic cancer cell debris that can induce inflammation by stimulating IL-1β release from tumor-associated macrophages via the TLR4/TRIF/NF-κB pathway ( 50 ). Furthermore, free Ig light chain (FLC) exerts an essential promotive effect on colitis-associated colon carcinogenesis by activating the inflammasome ( 91 ). The FLC blocker F991 can significantly impede the process of colon carcinogenesis by inhibiting the activation of the inflammasome and reducing the levels of cleaved caspase-1, IL-1β and IL-18.…”
Section: Cancer-derived Ig Performs Critical Roles In Cancer Progressmentioning
confidence: 99%
“…In addition, cancer-derived IgG is identified as a functional component of pancreatic cancer cell debris that can induce inflammation by stimulating IL-1β release from tumor-associated macrophages via the TLR4/TRIF/NF-κB pathway ( 50 ). Furthermore, free Ig light chain (FLC) exerts an essential promotive effect on colitis-associated colon carcinogenesis by activating the inflammasome ( 91 ). The FLC blocker F991 can significantly impede the process of colon carcinogenesis by inhibiting the activation of the inflammasome and reducing the levels of cleaved caspase-1, IL-1β and IL-18.…”
Section: Cancer-derived Ig Performs Critical Roles In Cancer Progressmentioning
confidence: 99%
“…Interestingly, increasing Igκ levels manifested in cytoplasmic filamentous network but remained dotted distribution around the nucleus in ConA-treated hepatocytes. Our previous results showed that FLCs were significantly increased in the colon tissue of dextran sulfate sodium salt (DSS)-induced colitis mice and that F991, an FLC inhibitor, significantly suppressed the progression of DSS-induced colitis [ 23 ]. The above data suggest that Igκ deposition in ConA-treated hepatocytes might be associated with inflammation and liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…This came about after realizing that immunoglobulin light chains may help elicit inflammation (38) and occur at increased levels in inflammatory pathologies (39). Anti-FLC peptide F991, a functional inhibitor of the immunoglobulin light chain either in its free form or when in IgE (40), appeared to be able to slow down the progression of colitis, presumably by reducing inflammation (41), but in our own hands, the results were variable. To try to understand both the effect and its complexity/variability, we constructed a detailed differential equation model (42).…”
Section: Introductionmentioning
confidence: 90%
“…Other than the one we developed and used here, there are no mathematical models that address the (lack of) ability of a peptide drug interfering with IgLC (or IgE) to revert chronic inflammation definitively. This non-robust ability has been the subject of a set of experimental studies by one of the authors of the present paper [ (38,39,65); see also (41)] and served as the inspiration and guidance for both the present and the previous paper (42). The present paper comes with another novelty however; it provides for an explanation of the faltering effects of this type of peptide as well as a number of suggestions on how to improve the robustness of this type of therapy.…”
Section: This Model's Noveltymentioning
confidence: 99%